Humidity-Sensing Material Cottonid – Microstructural Tuning for Improved Actuation and Fatigue Performance - Scholz, Ronja; Langhansl, Matthias; Zollfrank, Cordt; Walther, Frank (Frontiers in Materials, 2020)
Adaptive actuators are stimuli-responsive materials able to make a direct use of primary energy to produce motion, as it is well known from motile plant structures. Changes in environmental conditions, such as temperature and humidity, trigger passive movements without the need of metabolism or the use of electrical energy. This bioinspired adaptive mechanism is an alternative and sustainable approach in terms of energy conservation in technical applications. The cellulose-based functional material Cottonid is a promising candidate in this context. It is hygroscopic and possesses a process-related structural anisotropy, which results in direction-dependent actuation and fatigue performance. Since Cottonid is a modified natural material, its microstructure is tunable through chemical modification of the cellulose during the manufacturing process. To assess the influence of varying manufacturing parameters on the microstructure, the actuation behavior as well as the mechanical properties, a parameter study was carried out to identify the most promising modifications for stimuli-responsive element production while maintaining mechanical robustness. This was accomplished with respect to variations of the cellulose source, the chemical catalyst for cellulose modification, temperature of the catalyst bath Tcat as well as reaction time treact. Specimens’ microstructures were investigated with scanning electron microscopy, infrared spectroscopy as well as X-ray diffraction. The actuation behavior was characterized over instrumented experiments in a climate chamber in varying environmental conditions, whereas the environmental fatigue behavior was evaluated in tests with superimposed medial and mechanical loading. Obtained results identified Tcat as most influential process parameter onto resulting material actuation properties, which enables a limitation of the possible process window. The findings are used to develop tailored functional materials, where anisotropy and hygroscopicity can be adjusted through the manufacturing process.